TEACHING VOCABULARY AND LEXICAL COMPETENCE - Gil, Beatriz Daruj (2016)
It is discussed in this article, by means of a theoretical reflection followed by a proposal of teaching the lexicon, semantics, discursive and gramatical aspects that comprise the lexical competence. Contrary to the traditional educational practices that are based on the principle of lexical equivalence, this discussion shows that the knowledge of the word is not restricted to the semantic aspect, but extends to the paradigmatic and syntagmatic relations established by the word in its trajectory historical-discursive, to their grammatical properties, and to the conditions of production, movement and reception of the texts in which is updated.